TRANSLATORS AS MEDIATOR: CULTURAL NEGOTIATION IN TRANSLATING ENGLISH LITERARY TEXT INTO INDONESIAN - Nadia Khumairo Ma'shumah; Aulia Addinillah Arum; Arif Nur Syamsi (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
This study explores the translation of cultural-specific terms in the literary text as the translation process connects cultural differences between the source and target languages. Using Eco's notion of "translation as negotiation"; Bassnett's "translators as a mediator of cultures", and Newmark's cultural categorizations of terms as the framework and this qualitative study analyzed two Indonesian versions of the novel The Secret Garden by Francess Hodgson Burnett (1911). The first translated version was published in 2010 under the title "Taman Rahasia", whereas the second translated version was published in 2020 under the same title as the original version. This study has shown the complexity in closing the cultural gap between the source text and target text. As the impact, both translators used different forms of negotiation to accommodate readers' expectations and to functionally create optimal target texts in the target culture, which differentiate into five categories (i.e., ecological, material culture; social culture, social, politic, and administrative organizations; and gestures and habits).